Under lime : Simon Starling - Starling, Simon; Rosenberg, Angela; Cube Kunsthalle Berlin; Ausstellung Berlin, Temporäre Kunsthalle 2009-02,07 (Köln : König, 2009)
Angela Rosenberg: fortbewegung und dasein - progressing and existing Simon Starling: kakteenhaus, 2002 (details) Julian Heynen: drei arbeiten in berlin - three works in berlin Karl Blossfeldt: vintage prints Dominic Eichler: unterm dach beneath the raffers - installationsansichten installation views Simon Starling: eine kurze geschichte des kakteenhauses kakteenhaus - a brief history
anlässlich der Ausstellung Simon Starling: Under Lime, Temporäre Kunsthalle Berlin, 07.02.2009 - 18.03.2009
boek
Keywords: Starling, Simon